Relato integrado e a sustentabilidade de companhias abertas brasileiras: uma análise das empresas listadas no índice de sustentabilidade empresarial da B3 - Ferreira, Beatriz da Silva (2023)
The objective of this dissertation is to analyze the non-financial and sustainability information of the Integrated Report that are being disclosed by the companies listed in the Sustainability Index (ISE) of B3. In order to achieve the general objective of the study, a previous instrument developed by Santos and Miranda (2021) was used, in which key theoretical elements were defined for each of the types of capitals that represent the type of information associated with the non-financial capital of the RI. The research follows a mixed, qualitative and quantitative approach, with documentary research as a technical procedure. With the information obtained, an attempt was made to describe the content of the Integrated Reports, having analyzed 24 (twenty-four) companies in the period from 2016 to 2021, with the analysis of items related to non-financial information and sustainability contained in the IR. In the first phase of data collection, the structure, frequency and terms used in the Integrated Reports were mapped, the second stage comprised the document analysis, with the support of the Atlas.ti software, in the third phase the disclosure index was calculated with based on the theoretical elements of the non-financial capital of the Integrated Report. The key terms/theoretical elements of the non-financial capitals of the Integrated Report were identified in each of the 143 (one hundred and forty-three) reports in the coding stage carried out in the Atlas.ti software. The results of the study showed that the companies that stood out in the voluntary disclosure of the elements of the 4 (four) non-financial capitals of the IR were: Banco do Brasil, Cemig, Petrobras, Engie and Energias do Brasil (EDP). Among the non-financial capitals analyzed, the element “Social License” stands out in Social and Relationship Capital, where a disclosure index of ID=7.69% was identified, a relatively low number in relation to the other disclosed items. Despite the Social License being an important element for the social legitimacy of companies, only eleven organizations between 2016 and 2021 mentioned the Social License in their annual and sustainability reports, this result pointed to a lack in the reports regarding the approach to this topic. The study's findings also showed an evolution in the disclosure of the other theoretical elements over the years, there was a variation between 15.2% and 82.6% of the disclosed elements. Santander bank's annual report in 2021 had the lowest disclosure, while the 2020 annual sustainability report by Energias do Brasil (EDP) had the most disclosure in the analyzed period.